L’influenza del diritto criminale bizantino nel Codice di Dušan. 1349-1354 - ANGELINI, Paolo (Byzantina Symmeikta, 2012)
THE INFLUENCE OF THE BYZANTINE CRIMINAL LAW IN THE CODE OF DUSAN. 1349-1354 Stefan Dušan enacted the Code of Dušan in 1349. Its dispositions must be considered in relation with two Byzantine compilations that constituted the imperiale tripartite codification: the so-called Law of Justinian and to the Abridged syntagma. The Byzantine juridical influence must be considered very relevant in criminal law: public pain system, legal action ex officio by state, pain of death, physical punishments and mutilations, were juridical concepts and institutions unknown to Slav people before their convert to Christianity, and their introduction must be connected to the Byzantine religious, cultural and juridical influence. Considering the difference with Slav customary law (even if some elements derivating from it were preserved) and the connections with Greek-Roman compilations it can be underlined Dušan’s attempt to create and introduce in his empire a Byzantine legal system.